1986
DOI: 10.1083/jcb.102.1.112
|View full text |Cite
|
Sign up to set email alerts
|

Spatial organization of chromosomes in the salivary gland nuclei of Drosophila melanogaster.

Abstract: Abstract. Using a computer-based system for model building and analysis, three-dimensional models of 24Drosophila melanogaster salivary gland nuclei have been constructed from optically or physically sectioned glands, allowing several generalizations about chromosome folding and packaging in these nuclei. First and most surprising, the prominent coiling of the chromosomes is strongly chiral, with fight-handed gyres predominating. Second, high frequency appositions between certain loci and the nuclear envelope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
221
1
4

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(245 citation statements)
references
References 33 publications
(53 reference statements)
19
221
1
4
Order By: Relevance
“…locates telomeric loci near the surface of mammalian interphase nuclei (van Dekken et al, 1989). These and similar observations in other systems suggest that the ends of eukaryotic chromosomes are located close to the nuclear envelope (Agard and Sedat, 1983;Mathog et al, 1984;Foe and Alberts, 1985;Hochstrasser et al, 1986;Mathog and Sedat, 1989;Chung et al, 1990;Rawlins et al, 1991). This positioning throughout interphase in organisms as diverse as flies, trypanosomes, plants and mammals is likely to be a consequence of specific anchorage of telomeric DNA at the nuclear periphery.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…locates telomeric loci near the surface of mammalian interphase nuclei (van Dekken et al, 1989). These and similar observations in other systems suggest that the ends of eukaryotic chromosomes are located close to the nuclear envelope (Agard and Sedat, 1983;Mathog et al, 1984;Foe and Alberts, 1985;Hochstrasser et al, 1986;Mathog and Sedat, 1989;Chung et al, 1990;Rawlins et al, 1991). This positioning throughout interphase in organisms as diverse as flies, trypanosomes, plants and mammals is likely to be a consequence of specific anchorage of telomeric DNA at the nuclear periphery.…”
Section: Discussionsupporting
confidence: 73%
“…Rabl (1885) (Sperling and Ludtke, 1981;Cremer et al, 1982;Foe and Alberts, 1985). Furthermore, direct analysis of chromosome topography by three-dimensional microscopy indicates that the ends of interphase chromosomes are close to the nuclear envelope in a wide variety of eukaryotes (Agard and Sedat, 1983;Mathog et al, 1984;Hochstrasser et al, 1986;Mathog and Sedat, 1989;van Dekken et al, 1989;Chung et al, 1990;Rawlins et al, 1991). These cytological data suggest that telomeres could be attached to the nuclear envelope.…”
Section: Introductionmentioning
confidence: 99%
“…They compensate for incomplete DNA replication and contribute to the stability of chromosomes and karyotype (Muller, 1932;Pardue and Debaryshe, 1999;Biessmann and Mason, 2003). Telomeres also participate in nuclear architecture maintenance, and are known to associate with nuclear lamina (Hochstrasser et al, 1986;Marshall et al, 1996;Hari et al, 2001) or with nuclear matrix (de Lange, 1992;Luderus et al, 1996). However, the factors that underlie these phenomena, as well as the mechanisms of telomere functioning, remain poorly understood in Drosophila melanogaster.…”
mentioning
confidence: 99%
“…It is first described in nuclei of salamander larvae by Karl Rabl [16]. Rabl-like configuration also exists in other eukaryotic cells, such as Sacharomyces cerevisae [17], in the embryonic cells of Ascaris [18], in Drosophila melanogaster [19], in spermatocytes of the mosquito Aedes aegypti [20], fibroblasts of the treeshrew (Tupaia belangeri), the lymphocytes of the Indian muntjac, Chinese hamster fibroblasts [21], and some plants [22]. However, it was reported that chromosome alignment in Rabl configuration might not be important to control gene expression [23].…”
Section: Models For Interphase Chromosome Positioningmentioning
confidence: 99%